The cost-effectiveness of syphilis screening in pregnant women: a systematic literature review - Zhang, Meng; Zhang, Hongyan; Hui, Xiaoqing; Qu, Huimin; Xia, Junfen; Xu, Feng; Shi, Cannan; He, Junjian; Cao, Yuan; Hu, Mengcai (Frontiers in Public Health, 2024)
Introduction The cost-effectiveness study of syphilis screening in pregnant women has not been synthesized. This study aimed to synthesize the economic evidence on the cost-effectiveness of syphilis screening in pregnant women that might contribute to making recommendations on the future direction of syphilis screening approaches. Methods We systematically searched MEDLINE, PubMed, and Web of Science databases for relevant studies published before 19 January 2023 and identified the cost-effectiveness analyses for syphilis screening in pregnant women. The methodological design quality was appraised by the Consolidated Health Economic Evaluation Reporting Standards (CHEERS) 2022 checklist. Results In total, 17 literature met the eligibility criteria for a full review. Of the 17 studies, four evaluated interventions using different screening methods, seven assessed a combination of syphilis testing and treatment interventions, three focused on repeat screening intervention, and four evaluated the interventions that integrated syphilis and HIV testing. The most cost-effective strategy appeared to be rapid syphilis testing with high treatment rates in pregnant women who were positive. Discussion The cost-effectiveness of syphilis screening for pregnancy has been widely demonstrated. It is very essential to improve the compliance with maternal screening and the treatment rates for positive pregnant women while implementing screening.